WHAT’S WRONG WITH US? AN ANALYSIS OF INDONESIAN PRESIDENT JOKO WIDODO’S PUBLIC SPEECHES FROM 2017 TO 2018 - Adam Tyson; Stanislaus Apresian (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2021)
The research examines the rhetorical style and political priorities in Indonesian President Joko Widodo’s public speeches during his first term in office. Content analysis is used to investigate a purposive sample of 66 presidential speeches from May 2017 to May 2018. In addition, the research identifies the similarity of words to understand the selective appraisal of Indonesia’s progress based on President Jokowi’s utterances. In one contentious oration on May 18th, 2017, delivered to government officials, the president bluntly asked ‘what’s wrong with us’? The question presupposes that something is wrong in Indonesian politics, and is narrowcast to an audience of government officials, some of whom are implicated in the developmental shortcomings, administrative inefficiencies, and social conflicts that persist in Indonesia today. The president’s strategic message implies that Indonesia’s economic development unduly lags regional competitors; disinformation and hate speech create social divisions and political distortions; and there is a significant digital and technological divide in the country. The research result shows that the president’s passion extends beyond bureaucratic reform and into contentious political topics, where selective attempts at disruptive truth-telling are made.